(untitled) (Research, Society and Development, 2022)
Introduction: Nursing professionals must know their institutions and the corresponding laws of their profession. From the inspection point of view, in the care and administrative spheres, errors can occur that culminate in damages to the patient or other professionals. Objective: To analyze studies on ethical processes in Regional Nursing Councils published in the literature. Methodology: This is an integrative literature review carried out in the SciELO and MedLine databases and the other databases found in the VHL. Results: The sample had 08 articles, which analyzed, together, 05 Federative Units of the country. Despite the regional difference, the studies showed similar results. Most ethical processes were directed at nursing assistants and were about errors during drug administration or errors during tube procedures. In the processes aimed at nurses, the ethical panorama changed to moral harassment, abandonment of duty and irregular or illegal exercise of the profession. Final Considerations: The study of the profile of ethical processes in Nursing is essential to build targeted approaches that aim to minimize the occurrence of these.